A multi-centre, blinded, randomised, placebo-controlled, laboratory-based study of MQX-503, a novel topical gel formulation of nitroglycerine, in patients with Raynaud phenomenon. Issue 12 (25th December 2012) - Hummers, Laura K; Dugowson, Carin E; Dechow, Frederick J; Wise, Robert A; Gregory, Jeffrey; Michalek, Joel; Yenokyan, Gayane; McGready, John; Wigley, Fredrick M
Abstract : Objective: MQX-503 is a novel nitroglycerine preparation designed to absorb quickly and allow local vasodilatation in the skin. We examined the efficacy and tolerability of this medication in Raynaud phenomenon (RP) in a laboratory-based study. Methods: In this multi-centre, double-blind, randomised, placebo-controlled, cross-over study, subjects were treated with 0.5% or 1.25% nitroglycerine or placebo gel. Subjects received each dose twice in a randomised order. Each study session consisted of baseline laser Doppler measurements, study gel application and 5 min of cold chamber exposure (−20°C). Blood flow (BF) was measured at the end of exposure and for the next 120 min at set intervals. Other outcome measures included achievement of baseline BF; the time to achieve 50% and 70% baseline skin temperature (ST); and pain, tingling and numbness scores. Results: 37 subjects completed 214 treatment periods. Time to achieve baseline BF was significantly shorter in the two treated groups (HR=1.77 and 2.02 for 0.5% and 1.25% vs placebo, respectively). The proportion of subjects achieving baseline BF was 45.8% for placebo, 66.2% for 0.5% and 69% for 1.25% (p=0.01 and p=0.002 for 0.5% and 1.25% vs placebo, respectively). No meaningful differences were seen in ST or pain/numbness/tingling scores. Treatment was well tolerated with no serious adverse events. Conclusions: Treatment with MQX-503 caused a significant improvement in skin BF compared with placebo. Data from this proof of concept study suggest benefit of MQX-503 in subjects with RP.